RECOMMENDATIONS FOR PREVENTION AND CONTROL OF INFECTION IN NON-INVASIVE VENTILATION IN HOSPITAL ENVIRONMENT - Méndez, Lucía; Caneiras, Cátia; Oliveira Reis, Carla; Bernardes, Viviana (Health and Society, 2023)
There are numerous studies and recommendations on the complications associated with invasive mechanical ventilation, but few on prevention and control of infection in non-invasive ventilation (NIV), especially at the hospital environment. Healthcare workers (HCW) should be alert to the potential risk of transmission of infection in NIV. The main goal of this manuscript is to establish and promote good practices in the prevention and control of infections associated with NIV, as well as the development of a document that can serve as a guideline for HCW. A review of the literature on cleaning and disinfection of devices in NIV was carried out between February 2019 and August 2020 and the technical specifications of NIV devices, published by the manufacturers, were also analyzed. NIV devices require a high level of disinfection using chemical disinfectants. It is necessary to clean and disinfect the surface of the ventilator daily, while the rest of the components should be cleaned and disinfected with a weekly frequency. It should avoid active humidification when possible, favoring passive humidification. Using a bacteriological filter is extremely important in a hospital environment and should be considered. In patients with COVID-19, it is also recommended to use non-ventilated interfaces and 2 filters, one bacteriological at the outlet of the ventilator and another preferably Heat and Moisture Exchanging Filter (HMEF) in the interface. The cleaning and disinfection instructions for NIV are based on recommendations for decontamination of semi-critical material and basic infection control precautions. This document provides an orientation guide of the main procedures to be implemented in the prevention and control of infection in NIV that must be adapted to each hospital.